2005
DOI: 10.1152/ajpgi.00436.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electroneutral Na transport in sheep rumen epithelium by luminal ammonia

Abstract: Ammonia is an abundant fermentation product in the forestomachs of ruminants and the intestine of other species. Uptake as NH3 or NH4+ should modulate cytosolic pH and sodium-proton exchange via Na+/H+ exchanger (NHE). Transport rates of Na+, NH4+, and NH3 across the isolated rumen epithelium were studied at various luminal ammonia concentrations and pH values using the Ussing chamber method. The patch-clamp technique was used to identify an uptake route for NH4+. The data show that luminal ammonia inhibits el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 50 publications
11
66
2
Order By: Relevance
“…Past studies have shown that at the pH found physiologically in the rumen (<6.8), channel-mediated uptake of NH 4 + greatly exceeds efflux in the form of NH 3 [1] and efflux of protons via this pathway may contribute to ruminal pH homeostasis [4]. The purpose of the current study was to identify candidate genes for this conductance.…”
Section: Introductionmentioning
confidence: 93%
“…Past studies have shown that at the pH found physiologically in the rumen (<6.8), channel-mediated uptake of NH 4 + greatly exceeds efflux in the form of NH 3 [1] and efflux of protons via this pathway may contribute to ruminal pH homeostasis [4]. The purpose of the current study was to identify candidate genes for this conductance.…”
Section: Introductionmentioning
confidence: 93%
“…The mechanism responsible for this pH-dependent effect of ammonia cannot be determined from the experiments performed. However, it is very plausible that a large amount of ammonia is absorbed as NH 4 ϩ under low pH conditions (6), and the NH 4 ϩ dissociates into H ϩ and NH 3 in the cytosol (2). It is also possible that H ϩ and/or NH 3 exert effects on UT-B expression (3).…”
Section: Effect Of Ammonia and Urea On Mrna Expression And Protein Abmentioning
confidence: 99%
“…The incubation of rumen epithelium has been described in detail by Abdoun et al (2). Briefly, sheep were killed in a local slaughterhouse, and the reticulorumen was removed from the abdominal cavity within 2-3 min.…”
Section: Flux Measurements In the Ussing Chambermentioning
confidence: 99%
“…Chloride and mannitol fluxes were measured essentially as described previously (2,73,74). All measurements were performed under classical Ussing chamber conditions without chemical gradients and with transepithelial potential clamped to 0 mV in the short-circuit mode.…”
Section: Flux Measurements In the Ussing Chambermentioning
confidence: 99%
See 1 more Smart Citation